Not only Monte Testaccio: Reflections about the Presence of Baetican Olive Oil Amphorae in Rome (and Ostia) during the Middle Imperial Age (2nd–early 3rd Centuries AD) Emerging from the Findings at the ‘Terme di Elagabalo’ in Rome - Radaelli, Edoardo (Rzym a Półwysep Iberyjski: Inspiracje i powiązania na przestrzeni dziejów, 2021)
The quantities of Baetican amphorae Dressel 20 found in the Middle Imperial contexts (2nd–early 3rd centuries AD) discovered during the excavations in the so-called ‘Terme di Elagabalo’ in Rome are added to those discovered in other excavations carried out in Rome (outside Monte Testaccio) and Ostia in order to ponder over their presence in the two cities during this chronological period. Ancient sources and studies are also analysed so as to better understand this commodity, leading to a reflection upon the supply system to the Capital and the strategies of Emperors to improve it.